DAYAH MODERN: PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI PESANTREN TERPADU SERTA RELEVANSINYA DENGAN SEJARAH PENDIDIKAN ISLAM DI ACEH - Inayatillah Inayatillah (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2022)
The Islamic Religious Education (PAI) curriculum in integrated pesantren or modern pesantren (dayah modern) in Aceh is currently maturing itself through improving contextual learning, one of which is through the form of integrated pesantren. Islamic Religious Education in integrated Islamic boarding schools is structured in a pattern that is quite inclusive, by integrating science, philosophy and learning technology in understanding Islamic religious knowledge. This shift is presumably due to social, economic, cultural and political developments that have changed which have also led to changes in people's perceptions of religious knowledge. This research is a qualitative research, the data were obtained through a literature study by conducting a literature review on journals and books related to the topic. Furthermore, historical and contemporary data that have been collected will be used to reveal patterns of curriculum development for Islamic Religious Education in Aceh throughout history using qualitative descriptive analysis. The results of the study show that the history of Islamic education in Aceh has been reduced by the effects of the dichotomy of knowledge inherited from the colonial. At present, the curriculum that is continuously being refined is more directed to the needs of employment and makes Islamic boarding schools more acceptable